2014
DOI: 10.1177/1933719114526473
|View full text |Cite
|
Sign up to set email alerts
|

Genes Downregulated in Endometriosis Are Located Near the Known Imprinting Genes

Abstract: There is now accumulating evidence that endometriosis is a disease associated with an epigenetic disorder. Genomic imprinting is an epigenetic phenomenon known to regulate DNA methylation of either maternal or paternal alleles. We hypothesize that hypermethylated endometriosis-associated genes may be enriched at imprinted gene loci. We sought to determine whether downregulated genes associated with endometriosis susceptibility are associated with chromosomal location of the known paternally and maternally expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Consistent with this hypothesis, enhanced estrogenic activity and reduced progesterone responsiveness are considered to be involved in the etiology of endometriosis (11). Therefore, endometriosis is a chronic disease with substantial epigenetic dysregulation of decidualization susceptibility genes (4).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Consistent with this hypothesis, enhanced estrogenic activity and reduced progesterone responsiveness are considered to be involved in the etiology of endometriosis (11). Therefore, endometriosis is a chronic disease with substantial epigenetic dysregulation of decidualization susceptibility genes (4).…”
Section: Discussionmentioning
confidence: 90%
“…To date, two studies investigating this context have been published (4,38). Firstly, the presence of hypermethylated regions located at the ends of chromosomes among endometriosis samples suggested that the distribution pattern of the hypermethylation was not random (38).…”
Section: Mechanistic Link Between Genomic Imprinting and Endometriosimentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic imprinting; DNA methylation; histone modifications with different nominations (acetylation/ histone phosphorylation/histone ubiquitylation/ histone sumoylation); microRNAs [183] and recently discovered, stranded, noncoding RNAs (ncRNAs) [168]; transcription factor network; and chromatin remodeling are known to regulate transcription of target genes. Genomic imprinting is an epigenetic phenomenon known to regulate DNA methylation of either maternal or paternal alleles [184], and the male and female germ lines guide the allele-specific DNA methylation marking and histone modification onto specific gene regions of parental alleles [185]. The epigenome, the collection of DNA methylation, and the histone modifications can be influenced by environmental factors.…”
Section: Epigenetics In Endometriosis: Methylation Pattern Of Sexual mentioning
confidence: 99%